A modern pollen–climate calibration set from central‐western Mongolia and its application to a late glacial–Holocene record. (26th May 2014) - Tian, Fang; Herzschuh, Ulrike; Telford, Richard J.; Mischke, Steffen; Van der Meeren, Thijs; Krengel, Michael; Richardson, James
Abstract Aim Fossil pollen spectra from lake sediments in central and western Mongolia have been used to interpret past climatic variations, but hitherto no suitable modern pollen–climate calibration set has been available to infer past climate changes quantitatively. We established such a modern pollen dataset and used it to develop a transfer function model that we applied to a fossil pollen record in order to investigate: (1) whether there was a significant moisture response to the Younger Dryas event in north‐western Mongolia; and (2) whether the early Holocene was characterized by dry or wet climatic conditions. Location Central and western Mongolia. Methods We analysed pollen data from surface sediments from 90 lakes. A transfer function for mean annual precipitation (Pann) was developed with weighted averaging partial least squares regression (WA‐PLS) and applied to a fossil pollen record from Lake Bayan Nuur (49.98° N, 93.95° E, 932 m a.s.l.). Statistical approaches were used to investigate the modern pollen–climate relationships and assess model performance and reconstruction output. Results Redundancy analysis shows that the modern pollen spectra are characteristic of their respective vegetation types and local climate. Spatial autocorrelation and significance tests of environmental variables show that the WA‐PLS model for Pann is the most valid function for our dataset, and possesses the lowest root mean squared error of prediction. Main conclusions Precipitation is the most important predictor of pollen and vegetation distributions in our study area. Our quantitative climate reconstruction indicates a dry Younger Dryas, a relatively dry early Holocene, a wet mid‐Holocene and a dry late Holocene.